If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 13 = 7y + -2 Reorder the terms: 13 + 5y = 7y + -2 Reorder the terms: 13 + 5y = -2 + 7y Solving 13 + 5y = -2 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 13 + 5y + -7y = -2 + 7y + -7y Combine like terms: 5y + -7y = -2y 13 + -2y = -2 + 7y + -7y Combine like terms: 7y + -7y = 0 13 + -2y = -2 + 0 13 + -2y = -2 Add '-13' to each side of the equation. 13 + -13 + -2y = -2 + -13 Combine like terms: 13 + -13 = 0 0 + -2y = -2 + -13 -2y = -2 + -13 Combine like terms: -2 + -13 = -15 -2y = -15 Divide each side by '-2'. y = 7.5 Simplifying y = 7.5
| -2r-3=6r+4 | | n^2-2n-1=38.5 | | (x/11)=(x/12)-14 | | n^2-2n-2=38.5 | | 6g-4(-6+3g)=1-g | | -5p+6+6p=11 | | -3/5-3/10 | | 8.4x+16.28=-11.6+16.04 | | 3-/5-3/10 | | x^2+8x+8=3x+4 | | 24+16x=75+17x | | (2z-3)(z+4)=(3z-2)(z+6) | | (-5p+8)=(7p-5) | | 4x+2=3(x-3)+5 | | 0=-5t+15 | | 7.6x-1.1=29.3 | | 2[3-(-8x-8)]=80x+86 | | 1.7+x=7.1 | | 2+1x=1 | | 2l+2(70)=600 | | 4/5x-8=9/5x | | -2y-16=0 | | x^2-9x-14=-6x+4 | | 3/4*.1=8 | | 3(6z-1)-4(z+2)=6(z+1) | | x^2-2x-27=8 | | 2(56-13)= | | -1=b^4-7 | | Abs(x-2)=22 | | 1.92-0.33= | | 3-2/2--4 | | -8u=24 |